Computational Molecular Biology - Peter Clote (Wiley series in mathematical and computational biology., 2000)
"Primarily aimed at advanced undergraduate and graduate students from bioinformatics, computer science, statistics, mathematics and the biological sciences, this text will also interest researchers from these fields."--Jacket.